LAS MICRO Y PEQUEÑAS EMPRESAS ARTESANALES: LA PROBLEMÁTICA DEL MARCO LEGAL DE EXPORTACIÓN EN EL PERÚ EN LOS AÑOS 2010-2011 - Cruz Gonzales, Niko (2012)
The investigation is entitled “Micro and Small Craft: The problem of Legal Framework for Export in Peru, in the years 2010- 2011”. Its overall objective is to determine the legal framework of the micro and small craft firms for export purposes in our country, analysing the norms that regulates the structure and functioning of the MSES craft. The assumption of the investigation finds that the legal problems (three laws in less than 15 years) is the main cause of the limited capacity of micro and small enterprises engaged in the export. The methodology has revised the bibliography and statistics of the case, and has been applied a questionnaire to 260 micro entrepreneurs dedicated to the purchase- sell handicrafts, nationally and for export. Among the findings stipulated that the regulatory on the structure and functioning of the micro and small enterprises, in general, has been amended in the last 15 years, by three legal devices: the Law enacted in the Fujimori government (1997 that creates PROPYME); Act No. 28015 (2003) given in the Government of Toledo and the promulgated by Garcia, through the D. L. 1086 And its Regulations, through the D. L. NO in the year 2008. Among the findings stipulated that the regulatory on the structure and functioning of the micro and small enterprises, in general, has been amended in the last 15 years, by three legal devices: the Law enacted in the Fujimori government (1997 that creates PROPYME); Act No. 28015 (2003) given in the Government of Toledo and the promulgated by Garcia, through the D. L. 1086 And its Regulations, through the D. L. NO in the year 2008.